2013
DOI: 10.1002/eji.201242505
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib and doxorubicin enhance the Stat1‐dependent antitumor immune response

Abstract: Additional supporting information may be found in the online version of this article at the publisher's web-site IntroductionThe reversal of immune tolerance represents one central goal in cancer immune therapies and serves as a rationale for developing [3,5]. Furthermore, these drugs can enhance the immunogenicity of the tumor epithelium, and as well change the immunosuppressive cytokine milieu produced by the tumor and its microenvironment, thereby facilitating the maturation and function of effector cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 41 publications
10
98
0
Order By: Relevance
“…Considering the implications in cancer treatment, Stat1's response to chemotherapeutic drugs is likely to be controlled by both cell-autonomous and immune regulatory mechanisms. This notion is supported by a recent study showing that efficient treatment of ErbB2/HER2 mouse mammary tumors with the RTK inhibitor lapatinib and doxorubicin requires the immune regulatory function of Stat1 (14). Nevertheless, Stat1's function in drug-sensitive cells may be different from its function in drug-resistant tumor cells.…”
Section: Stat1 Protects Cells From the Antiproliferative Effects Of Amentioning
confidence: 94%
See 1 more Smart Citation
“…Considering the implications in cancer treatment, Stat1's response to chemotherapeutic drugs is likely to be controlled by both cell-autonomous and immune regulatory mechanisms. This notion is supported by a recent study showing that efficient treatment of ErbB2/HER2 mouse mammary tumors with the RTK inhibitor lapatinib and doxorubicin requires the immune regulatory function of Stat1 (14). Nevertheless, Stat1's function in drug-sensitive cells may be different from its function in drug-resistant tumor cells.…”
Section: Stat1 Protects Cells From the Antiproliferative Effects Of Amentioning
confidence: 94%
“…One mechanism depends on the induction of antitumor immune responses (6) and the other on the suppression of oncogenic signaling in a cell-autonomous (tumor cell-specific) manner (7)(8)(9)(10)(11). The antitumor properties of Stat1 have been best documented in breast cancers in which Stat1 assumes both immune regulatory and cell-autonomous functions to suppress either ErbB2/HER2 or estrogen receptor α (ERα)-mediated tumorigenesis (4,(10)(11)(12)(13)(14). Stat1 can also act as a promoter of mouse leukemogenesis caused by the activation of either Abelson murine leukemia viral oncogene homolog v-Abl or translocation-Ets-leukemia locus (TEL) and Janus kinase 2 fusion protein through immune regulatory mechanisms independent of IFN-γ (15).…”
mentioning
confidence: 99%
“…Conversely, CD4 + T cell depletion further delays MMTV-Neu tumor growth in mice treated with doxorubicin and lapatinib -a small molecule inhibitor of EGFR and ERBB2 [71]. The importance of CD4 + cells following paclitaxel or doxorubicin, without the addition of IDO inhibtors or lapatinib, remains to be established in mammary tumor-bearing MMTV-Neu mice, since these controls were not included in either study [70,71].…”
Section: Adaptive Immune Cellsmentioning
confidence: 99%
“…The importance of CD4 + cells following paclitaxel or doxorubicin, without the addition of IDO inhibtors or lapatinib, remains to be established in mammary tumor-bearing MMTV-Neu mice, since these controls were not included in either study [70,71]. Nonetheless, manipulation of Th17 cells or other CD4 + T cell subsets may be a useful strategy to combat cancer growth and metastasis when used in combination with chemotherapy.…”
Section: Adaptive Immune Cellsmentioning
confidence: 99%
“…Experiments in mouse cancer models have shown that STAT1 can function as a tumor suppressor via mechanisms that depend on the induction of antitumor immune responses as well as the inhibition of oncogenic signaling in a cell-autonomous (cell-specific) manner (8,9). The antitumor properties of STAT1 have been best characterized in mouse models of breast cancer, in which STAT1 assumes both immunoregulatory and cell-autonomous functions to suppress tumor formation by either ErbB2/HER2 or estrogen receptor a (8,10). Contrary to its antitumor effects in breast cancer, STAT1 promotes leukemogenesis in mice expressing v-ABL or TEL-JAK2 by increasing MHC class I expression and inhibiting tumor clearance by the immune system (11).…”
Section: Introductionmentioning
confidence: 99%